Effect of simulated tennis steps and slides on tread element friction and wear - Hale, J.; Lewis, R.; Carré, M. J. (Sports Engineering, 2021)
In hard court tennis, players change direction by either stepping or sliding. The shoe-surface friction during these movements is crucial to player performance. Too little friction when stepping may result in a slip. Too much friction when attempting to slide could cause the player to move only a short distance, or to fail to slide. To understand the influence of tread design on shoe-surface friction in tennis, experiments were performed on individual shoe tread elements that replicated the tribological conditions typically experienced during hard court step and slide movements. Tread element orientation had no effect on the static friction in step movements, but longer tread elements (in the sliding direction) had 9% lower dynamic friction during slide movements (p < 0.001). The friction between tennis shoe tread and hard court tennis surfaces is also shown to be influenced by the tread`s sliding history, and the wearing pattern that forms on the surface of the rubber.